Effects of preventive UV-inflammation on the development and productivity of potatoes - Семенов, А. О.; Кожушко, Г. М.; Сахно, Т. В. (Scientific Progress & Innovations, 2018)
The effect of ultraviolet (UV) irradiation on potato tubers before planting is investigated. Experimental studies were conducted on medium-early potato varieties «Utro raneie» and «Rocco» using ultraviolet mercury discharge lamps of low pressure. It was established that in plants with irradiated tubers, which before irradiation at a dose of 120–240 J/m2, early roots were formed and developed. In addition, plants increase vegetative growth and increase yields.